Catechol and Humic Acid Sorption onto a Range of Laboratory-Produced Black Carbons (Biochars) - Kasozi, Gabriel N; Zimmerman, Andrew R; Nkedi-Kizza, Peter; Gao, Bin (Environmental science & technology, 2010)
Although the major influence of black carbon (BC) on soil and sediment organic contaminant sorption is widely accepted, an understanding of the mechanisms and natural variation in pyrogenic carbon interaction with natural organic matter (NOM) is lacking. The sorption of a phenolic NOM monomer (catechol) and humic acids (HA) onto BC was examined using biochars made from oak, pine, and grass at 250, 400, and 650 °C. Catechol sorption equilibrium occurred after 14 d and was described by a diffusion kinetic model, while HA required only 1 d and followed pseudo-second-order kinetics. Catechol sorption capacity increased with increasing biochar combustion temperature, from pine < oak < grass and from coarse < fine particle size. At lower catechol concentrations, sorption affinity (Freundlich constant, K f) was directly related to micropore surface area (measured via CO2 sorptometry) indicating the predominance of specific adsorption. In contrast, HA exhibited an order of magnitude less sorption (0.1% versus 1%, by weight) due to its exclusion from micropores. Greater sorption of both catechol and HA occurred on biochars with nanopores, i.e. biochars made at higher temperatures. These findings suggest that addition of BC to soil, via natural fires or biochar amendments, will sequester abundant native OM through sorption.